Implications of Transfer Pricing on Taxpayer Compliance and Corporate Tax Avoidance - Rafiriko Siagian; Tiolina Evi Nausta Pardede (Manunggal Halim Jaya, 2026)
Transfer pricing is a strategic issue in corporate taxation, especially for entities that have special relationships and decentralized business structures. On the one hand, transfer pricing serves as a managerial mechanism for cost control, performance evaluation, and internal decision-making. However, on the other hand, transfer pricing has the potential to be used as an aggressive tax planning instrument that has an impact on taxpayer compliance and increasing tax avoidance practices. This study aims to analyze the implications of transfer pricing on taxpayer compliance and corporate tax avoidance through a literature review approach. Data sources were obtained from national and international journals for the 2020–2024 period that are relevant to the topics of transfer pricing, tax compliance, and tax avoidance. The analysis method is carried out through a descriptive-qualitative synthesis of previous research findings. The results of the study show that the implementation of transfer pricing oriented to the principles of fairness and business practice tends to increase the formal and material compliance of taxpayers through transparency and accountability of tax reporting. In contrast, aggressive transfer pricing practices contribute to increased corporate tax avoidance, especially through the mechanism of profit transfer between entities within a single business group. This research provides a conceptual contribution by affirming the dual role of transfer pricing as a management control instrument and tax planning tool, as well as providing implications for tax authorities and corporate management in designing transfer pricing policies that are balanced between efficiency and compliance.